Zeno crossovers in the entanglement speed of spin chains with noisy impurities - Chaudhari, Abhijit P; Kelly, Shane P.; Valencia, Tortora, Riccardo J; Marino, Jamir (Institute of Physics, 2022)
We use a noisy signal with finite correlation time to drive a spin (dissipative impurity) in the quantum XY spin chain and calculate the dynamics of entanglement entropy (EE) of a bipartition of spins, for a stochastic quantum trajectory. We compute the noise averaged EE of a bipartition of spins and observe that its speed of spreading decreases at strong dissipation, as a result of the Zeno effect. We recover the Zeno crossover and show that noise averaged EE can be used as a proxy for the heating and Zeno regimes. Upon increasing the correlation time of the noise, the location of the Zeno crossover shifts at stronger dissipation, extending the heating regime.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: entanglement entropies; quantum dissipative systems; solvable lattice modelsspin; spin chains, ladders and planes